Analyzing the impact of the NCAA Selection committee`s new quadrant system - Reinig, B. A.; Horowitz, I. (Journal of Sports Analytics, 2019)
In 2018 the NCAA introduced a new metric, namely a four-Quadrant system intended to adjust for home-court advantage when assessing quality wins in the selection and seeding process for the Division I Men`s Basketball Tournament. We apply a linear programming procedure for ranking potential candidates for the tournament, based upon the traditional criteria, show how the rankings change with the inclusion of the Quadrant metric, and conclude that the metric has a substantial impact on the choices. We go on to show that the new ranking and choices are much more in sync with the NCAA Selection Committee`s actual ranking and choices than had been the case absent the metric, leading to the inference that the metric played an important role in the Committee`s decision making.